Feeding Manila in peace and war, 1850-1945 - Doeppers, Daniel F. 1938- (Quezon City Ateneo De Manila University Press, 2016)
Policymakers and scholars have come to realize that getting food, water, and services to the millions who live in the world's few dozen megacities is one of the twenty-first century's most formidable challenges. As these populations continue to grow, apocalyptic scenarios-sprawling slums plagued by hunger, disease, and social disarray-become increasingly plausible. In Feeding Manila in Peace and War, 1850-1945, Daniel F. Doeppers traces nearly a century in the life of Manila, one of the world's largest cities, to show how it grew and what sustained it. Doeppers follows key commodities for the city-rice, produce, fish, fowl, meat, milk, flour, coffee-and their complex interconnections. In the process he considers the changing ecology of the surrounding region as well as the social fabric that weaves together farmers, merchants, transporters, storekeepers, and door-to-door vendors.
Includes bibliographical references and index.
Keywords: Food supply -- History. -- Philippines -- Manila; Manila (Philippines) -- History -- 19th century; Manila (Philippines) -- History -- 20th century; Manila (Philippines) -- Social conditions -- 19th century; Manila (Philippines) -- Social conditions -- 20th century